On a general convergence for Broyden like update method - Rabindranath Sen; Rini Chattopadhyay; Tripti Saha (International Journal of Mathematics and Mathematical Sciences)
The role of Broyden's method as a powerful quasi-Newton method for solving unconstrained optimization problems or a system of nonlinear algebraic equations is well known. We offer here a general convergence criterion for a method akin to Broyden's method in Rn. The approach is different from those of other convergence proofs which are available only for the direct prediction methods.